DAMPAK KEBIJAKAN TATA RUANG TERHADAP PENGELOLAAN LINGKUNGAN HIDUP DI KABUPATEN GAYO LUES - Fadhlinsyah, Fadhlinsyah; Hajar, Siti (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2024)
This research discusses the impact of spatial planning policies on environmental management in Gayo Lues Regency. Spatial planning policy is an important instrument in determining sustainable and environmentally sound land use. Gayo Lues Regency, with its natural wealth and biodiversity, faces challenges in maintaining a balance between development and environmental conservation. This research uses a qualitative approach with a case study method, reviewing various policy documents, interviews with related parties, and field observations. The research results show that the implemented spatial planning policies have a significant impact on environmental management. Appropriate policies can improve natural resource management, reduce environmental degradation, and encourage sustainable development. However, there are also challenges in implementing policies, such as lack of coordination between institutions, limited resources, and conflicts of interest between economic development and environmental conservation. Thus, improvements are needed in the planning process, increased institutional capacity, and active community participation to achieve sustainable development goals in Gayo Lues Regency.